Tanaidacea (Crustacea: Peracarida) from Japan. II. Tanaidomorpha from the East China Sea, the West Pacific Ocean, and the Nansei Islands - Larsen, K., & Shimomura, M. (Zootaxa, 2007)
The Japanese shallow water fauna of tanaidomorphan Tanaidacea are examined. Seven new species Tumidochelia knighti, Mesotanais birdi, Leptognathia bamberi, Typhlotanais magdalensis, Typhlotanais ohtsukae, Tanaella kommritzia and Chauliopleona hansknechti are described. Chauliopleona dentata Dojiri & Sieg, 1997, from the type locality (California) is re-described. Leptognathia dentifera and L. unicinata are transferred to Tumidochelia. The genus Leptognathia is redefined and a number of species removed from the genus. The new leptognathid genera Biarticulata and Forcipatia are erected. A key to the Tumidochelia, Mesotanais, Leptognathia sensus stricto, and Forcipatia is given.